Developing Relational Pedagogical Techniques in Comparative Christian–Muslim Courses - Nickel, Breanna J. (Teaching theology and religion, 2024)
The article acknowledges the limits of the categories of similarity and difference in undergraduate comparative religion courses. To challenge these limitations, including the potential for dualistic or “us/them” thinking, several pedagogical attempts to increase relationality in Christian–Muslim courses are explored. Relational methods include emphasizing living and public interreligious conversations during class segments on scriptural figures as well as humanizing perpetrators of religiously motivated violence.